A Rare Case of Composite Dural Extranodal Marginal Zone Lymphoma and Chronic Lymphocytic Leukemia/Small Lymphocytic Lymphoma - Bustoros, Mark; Liechty, Benjamin; Zagzag, David; Liu, Cynthia; Shepherd, Timothy; Gruber, Deborah; Raphael, Bruce; Placantonakis, Dimitris G. (Frontiers in Neurology, 2018)
Background: Primary extranodal marginal zone lymphoma (MZL) of the dura is a rare neoplastic entity in the central nervous system (CNS). Methods: We used literature searches to identify previously reported cases of primary dural MZL. We also reviewed clinical, pathologic and radiographic data of an adult patient with concurrent dural MZL and chronic lymphocytic leukemia (CLL)/small lymphocytic lymphoma (SLL). Results: We identified 104 cases of dural MZL in the literature. None of them presented concurrently with another type of Non-Hodgkin lymphoma. This is the first report of composite lymphoma consisting of dural MZL and CLL/SLL in the bone marrow and lymph nodes. Conclusions: Primary dural MZL is a rare, indolent low-grade CNS lymphoma, with a relatively good prognosis. Its treatment is multidisciplinary and often requires surgical intervention due to brain compression, along with low to moderate doses of radiotherapy and/or systemic chemotherapy.